Barreras socioculturales de acceso al Servicio de Profilaxis Pre Exposición al VIHre Exposición al VIH - Moreno Soto, Manuel Felipe; Delgado-Castillo, Dianelys (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2025)
Background: although "pre-exposure prophylaxis" has been developed as a prevention strategy in the field of human immunodeficiency virus the negative influence of sociocultural barriers is still observed today.. Objective: to identify sociocultural barriers that limit access to HIV pre-exposure prophylaxis in Santiago de Cubas. Methods: a cross-sectional, descriptive, observational study was conducted with a population of 42 subjects. Six qualitative variables were analyzed. The results were presented in two-way tables. The percentage was used as a summary measure. The Chi-square test of independence was applied. Results: in the distribution of respondents by sexual orientation and gender, it was observed that men were primarily distributed among heterosexual and bisexual individuals. There was a dependent relationship between perceptions of inclusion and access to pre-exposure prophylaxis for the human immunodeficiency virus and the presence of psychosocial risk factors, the subjects’ educational level, and their classification as key populations. The majority of respondents reported being between not at all, little, and somewhat informed on the topic. Men who have sex with men predominated as the key population in the series. Conclusions: the sociocultural barriers that limit access to pre-exposure prophylaxis for the human immunodeficiency virus, are related to low educational levels and the presence of psychosocial risk factors in key populations.